Curcumin-loaded galactosylated BSA nanoparticles as targeted drug delivery carriers inhibit hepatocellular carcinoma cell proliferation and migration - Huang Y (Dove Medical Press, 2018)
Yike Huang,1 Lu Hu,2 Shan Huang,1 Wanjun Xu,1 Jingyuan Wan,2 Dandan Wang,1 Guocan Zheng,3 Zhining Xia1 1Department of Pharmaceutical Analysis, School of Pharmaceutical Sciences and Innovative Drug Research Centre, Chongqing University, Chongqing, China; 2Department of Pharmacology, Chongqing Key Laboratory of Biochemistry and Molecular Pharmacology, School of Pharmacy, Chongqing Medical University, Chongqing, China; 3Analytical and Testing Center, Chongqing University, Chongqing, China Background: The main objective of this study was to develop novel BSA nanoparticles (BSA NPs) for improving the bioavailability of curcumin as an anticancer drug, and those BSA NPs were galactosylated for forming the curcumin-loaded galactosylated BSA nanoparticles (Gal-BSA-Cur NPs), thus enhancing their ability to target asialoglycoprotein receptor (ASGPR) overexpressed on hepatocellular carcinoma (HCC) cells. Materials and methods: Gal-BSA-Cur NPs were prepared by the desolvation method and showed a spherical shape and well distribution with the average particle size of 116.24 nm. Results: In vitro drug release assay exhibited that Gal-BSA-Cur NPs had higher release rates and improved the curcumin solubility. Cell uptake studies confirmed that Gal-BSA-Cur NPs could selectively recognize receptors on the surface of HCC (HepG2) cells and improve internalization ability of drug compared with BSA NPs-loaded curcumin (BSA-Cur NPs), which might be due to high affinity to galactose. Further, the effects of Gal-BSA-Cur NPs were evaluated by cytotoxicity assay, crystal violet assay, cell apoptosis assay, and wound healing assay, respectively, which revealed that Gal-BSA-Cur NPs could inhibit HepG2 cells proliferation, induce cell apoptosis, and inhibit cell migration. Conclusion: Immunofluorescence staining has proved that the effects of Gal-BSA-Cur NPs related to the suppression of the nuclear factor κB-p65 (NF-κB-p65) expression in HepG2 cell nucleus. Therefore, these results indicate that novel Gal-BSA-Cur NPs are potential candidates for targeted curcumin delivery to HCC cells. Keywords: albumin, curcumin, nanoparticles, galactosylated, hepatocellular carcinoma